Mindfulness cognitive-based therapy combined with metaphor therapy can improve problematic social media use - Xiong, Weirui; Yu, Lu; Chai, Jinhui (Frontiers in Psychiatry, 2025)
IntroductionProblematic Social Media Use (PSMU) refers to an individual’s long-term, high-intensity use of social media. Although this behavior is not pathological, it has a negative impact on the physical and mental health of individuals. In the past, intervention methods used for PSMU often controlled behavior to reduce the usage time of individual social media platforms. However, because psychological needs satisfaction and unreasonable cognition that lead to the problematic use of social media by individuals are not considered, behavior-based treatment models often do not address this problem.Method30 participants with PSMU (with another 30 participants as a control group) participated in an intervention program of mindfulness-based cognitive therapy (MBCT) combined with metaphor therapy (MT).ResultsThe results showed that these therapies changed the participants’ cognition and behavior and achieved a good intervention effect.ConclusionThe MBCT combined with MT can be used as an intervention for patients with PSMU.